Analisis Persepsi Mahasiswa terhadap Penggunaan ChatGPT sebagai Alat Bantu Pembelajaran di Perguruan Tinggi - Nadia Putri Yasmin; Neza Faqiyah Almah; Novita Sari (CV. Shofanah Media Berkah, 2025)
The development of Artificial Intelligence (AI) technology is currently growing rapidly and has a significant impact on higher education, one form of its application is ChatGPT as a learning support tool. Students utilize ChatGPT to assist in understanding learning materials, completing academic assignments, and improving learning efficiency. This study aims to determine students’ perceptions of the use of ChatGPT as a learning support tool in higher education. A descriptive quantitative approach was employed by distributing a Likert-scale questionnaire to 30 undergraduate students. The research instrument consisted of eight items measuring perceived usefulness, ease of use, and impact on learning. Data were analyzed using descriptive statistics and reliability testing. The results indicate that students have positive perceptions of ChatGPT, with mean scores categorized as high to very high. The reliability test yielded a Cronbach’s Alpha value of 0.884, indicating excellent internal consistency. These findings suggest that ChatGPT is an effective and well-accepted learning support tool for university students.